Review of the genus Trichactia Stein (Diptera: Tachinidae) in the Palaearctic Region, with the description of a new species from Iran and the East Mediterranean - Gilasian, Ebrahim; Ziegler, Joachim; Parchami-Araghi, Mehrdad (Zootaxa, 2018)
The genus Trichactia Stein, 1924 (Diptera: Tachinidae) is newly recorded from Iran and its Palaearctic species are reviewed. The new species Trichactia meridiana Ziegler & Gilasian, sp. nov. is described from Iran and the East Mediterranean. An identification key to the three known Palaearctic species of Trichactia, photographs of all species and illustrations of their male terminalia are provided. Intraspecific variation between different geographical populations of T. meridiana sp. nov. is discussed.